Dept. of speculation - Offill, Jenny 1968- (Granta, 2014)
"Dept. of Speculation is a portrait of a marriage. It is also a beguiling rumination on the mysteries of intimacy, trust, faith, knowledge, and the condition of universal shipwreck that unites us all. Jenny Offill's heroine, referred to in these pages as simply "the wife," once exchanged love letters with her husband, postmarked Dept. of Speculation, their code name for all the uncertainty that inheres in life and in the strangely fluid confines of a long relationship. As they confront an array of common catastrophes...a colicky baby, bedbugs, a faltering marriage, stalled ambitions...the wife analyzes her predicament, invoking everything from Keats and Kafka to the thought experiments of the Stoics to the lessons of doomed Russian cosmonauts. She muses on the consuming, capacious experience of maternal love, and the near total destruction of the self that ensues from it, as she confronts the friction between domestic life and the seductions and demands of art. With cool precision, in language that shimmers with rage and wit and fierce longing, Jenny Offill has crafted an exquisitely suspenseful love story that has the velocity of a train hurtling through the night at top speed. Exceptionally lean and compact, Dept. of Speculation can be read in a single sitting, but there are enough bracing emotional insights in these pages to fill a much longer novel. "..
Keywords: FICTION / Literary; FICTION / Family Life; FICTION / Psychological; Marriage -- Fiction; Family life -- Fiction; Domestic fiction; Psychological fiction; Fiktionale Darstellung